Estimation of gap resonance relevant to side-by-side offloading. (1st April 2018) - Zhao, Wenhua; Pan, Zhiyuan; Lin, Frank; Li, Binbin; Taylor, Paul H.; Efthymiou, Mike
Abstract: Side-by-side offloading is becoming a more and more important offshore operation, where one vessel is moored alongside another one, forming a narrow gap between them. Using different types of incident waves, i.e. white noise waves, transient wave groups and regular waves, we investigated both the transient and steady-state resonant responses of the fluid in narrow gaps at model scale. The nonlinearity and uncertainties in obtaining the response amplitude operators (RAOs) of resonant fluid motions in narrow gaps are addressed. It appears that transient wave group testing is a promising approach for the investigation of gap resonance problem, because it avoids unwanted wave reflection induced by the limitation in the size of wave basins. To predict the gap resonant RAOs numerically, artificial damping is introduced into three different potential flow solvers to damp the otherwise over-estimated free surface motions in narrow gaps. The predicted RAOs, which are based on the potential flow solvers with the addition of calibrated damping, then show satisfactory agreement with the experimental data for a series of narrow gaps. This result confirms the reliability of the potential flow solvers in predicting gap resonant response (at model scale) for narrow gap widths that are relevant to engineering practice. Highlights: Gap resonance is investigated focusing on narrow gaps of practical application. Both numerical simulations and large scale model tests are conducted. Both steady-state and transient responses are investigated. Transient wave group test appears to be promising for gap resonance problem. Different ways of introducing artificial damping are evaluated.